Comparison of Repeated Fluid-Air Exchange and Passive Drainage for Removing Residual Emulsified Silicone Oil Droplets - Jian Yu; Yuan Zong; Ye Tan; Chunhui Jiang; Gezhi Xu (Journal of Ophthalmology, 2020)
Purpose. To compare the efficacy of passive drainage (PD) and repeated fluid-air (FA) exchange for removing emulsified silicone oil (SO) droplets. Methods. Twenty rhegmatogenous retinal detachment (RRD) patients who underwent primary pars plana vitrectomy (PPV) with SO tamponade were randomly and evenly divided into two groups for PD and FA exchange. Once the bulk of SO was removed, the first 2 mL of the washout fluid was collected, and then, another 2 mL of the washout fluid was collected after PD or FA exchange. The size and number of SO droplets in the washout fluid were measured using a Coulter counter (Multisizer 3, Beckman Coulter, Indianapolis, IN, USA). The efficiencies of FA exchange and PD for removing emulsified SO were compared. Results. The number of SO droplets decreased significantly after FA exchange and PD. The decrease in the number of droplets was statistically significant for larger droplets (>4 µm) with PD and for all droplet sizes with FA exchange. The decrease in the number of SO droplets of <4 μm was significantly greater with FA exchange than with PD. However, at the end of the procedure, the overall number and size distribution of SO droplets were similar for both procedures. Conclusions. PD and FA exchange reduced the number of residual emulsified SO droplets after SO tamponade efficiently. FA exchange may have some advantages over PD in removing small droplets.